Meningkatkan Keterampilan Proses Sains dalam Pembelajaran IPA Materi Energi Listrik pada Peserta Didik Kelas Ix-C SMPN 1 Bojongsoang Bandung Tp. 2021/2022 Melalui Penerapan Model Problem Based Instruction - Shofwati, Yayan Inayah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This research addresses the main issue of the low Science Process Skills of ninth-grade students in class IX-C at SMPN 1 Bojongsoang. The research results indicate an improvement in Science Process Skills after the implementation of the Problem-Based Instruction model. The implementation utilizes a student-centered learning approach to real-life problems, enabling students to develop thinking skills, problem-solving abilities, intellectual skills, and learn various roles through experiential learning in real-life situations. The students' Science Process Skills before the intervention were still low. The abilities to observe, classify, predict, use tools/materials, apply concepts, and communicate in the pre-cycle averaged 58.7. In Cycle I, there was an increase in the average learning outcomes of students to 71.3, and in Cycle II, the change further increased to 79.8. The students' learning completeness also improved after applying the Problem-Based Instruction model, which initially was only 17.6% in the pre-cycle, increased to 58.8% in Cycle I, and further improved to 85.3% in Cycle II. These results demonstrate that the Problem-Based Instruction model can enhance students' Science Process Skills in science lessons, particularly in the topic of electrical energy.